How Motivation and Social Interaction Shape Online Consumer Behavior: Evidence From E-WOM and Repurchase Intention - Khouroh, Umu; Ratnaningsih, Christina Sri; Windhyastiti, Irany; Zainal Shukri, Wan-Hafiz Wan (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study investigates how motivation to enter online markets and social interaction shape consumer behavior, with particular focus on electronic word-of-mouth (e-WOM) and repurchase intention. Drawing on social exchange theory and the theory of planned behavior, this research examines how motivational and social factors influence consumers’ behavioral outcomes in Indonesia’s rapidly expanding digital marketplace. Using data collected from 111 online consumers between 2024 and 2025, the study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed relationships. The findings reveal that consumer motivation strongly enhances social interaction, stimulates positive e-WOM, and increases repurchase intention. Social interaction also reinforces the effects of motivation by facilitating trust, communication, and community engagement. The model demonstrates satisfactory reliability, convergent validity, and discriminant validity, with substantial explanatory power for all constructs. The results highlight that both motivation and social connection are key mechanisms driving consumer loyalty and advocacy in online marketplaces. The study offers theoretical and managerial insights into how digital platforms can leverage motivation and social engagement to sustain long-term consumer relationships.